Caring for patients with pain during the COVID‐19 pandemic: consensus recommendations from an international expert panel. (26th April 2020) - Shanthanna, H.; Strand, N. H.; Provenzano, D. A.; Lobo, C. A.; Eldabe, S.; Bhatia, A.; Wegener, J.; Curtis, K.; Cohen, S. P.; Narouze, S.
Summary: Chronic pain causes significant suffering, limitation of daily activities and reduced quality of life. Infection from COVID‐19 is responsible for an ongoing pandemic that causes severe acute respiratory syndrome, leading to systemic complications and death. Led by the World Health Organization, healthcare systems across the world are engaged in limiting the spread of infection. As a result, all elective surgical procedures, outpatient procedures and patient visits, including pain management services, have been postponed or cancelled. This has affected the care of chronic pain patients. Most are elderly with multiple comorbidities, which puts them at risk of COVID‐19 infection. Important considerations that need to be recognised during this pandemic for chronic pain patients include: ensuring continuity of care and pain medications, especially opioids; use of telemedicine; maintaining biopsychosocial management; use of anti‐inflammatory drugs; use of steroids; and prioritising necessary procedural visits. There are no guidelines to inform physicians and healthcare providers engaged in caring for patients with pain during this period of crisis. We assembled an expert panel of pain physicians, psychologists and researchers from North America and Europe to formulate recommendations to guide practice. As the COVID‐19 situation continues to evolve rapidly, these recommendations are based on the best available evidence and expert opinion at this present time and may need adapting to local workplace policies.